Como nascem as sementes...Conhecendo o João e o pé de feijão - BONIATTI , ADRIANA; LUCIA TABILE , VERA; SOUZA DA SILVA , CINTIA (Salão do Conhecimento, 2021)
Projeto de investigação com as crianças: relato de experiência.